Cytoplasmic localization of prostate-specific membrane antigen inhibitors may confer advantages for targeted cancer therapies - Matthias, Jessica; Engelhardt, Johann; Schäfer, Martin; Bauder-Wüst, Ulrike; Meyer, Philipp Tobias; Haberkorn, Uwe; Eder, Matthias; Kopka, Klaus; Hell, Stefan; Eder, Ann-Christin (Cancer research, 2021)
Graphical Abstract - Download figureOpen in new tabDownload powerpoint - - Targeted imaging and therapy approaches based on novel prostate-specific membrane antigen (PSMA) inhibitors have fundamentally changed the treatment regimen of prostate cancer. However, the exact mechanism of PSMA inhibitor internalization has not yet been studied, and the inhibitors' subcellular fate remains elusive. Here, we investigated the intracellular distribution of peptidomimetic PSMA inhibitors and of PSMA itself by stimulated emission depletion (STED) nanoscopy, applying a novel nonstandard live cell staining protocol. Imaging analysis confirmed PSMA cluster formation at the cell surface of prostate cancer cells and clathrin-dependent endocytosis of PSMA inhibitors. Following the endosomal pathway, PSMA inhibitors accumulated in prostate cancer cells at clinically relevant time points. In contrast with PSMA itself, PSMA inhibitors were found to eventually distribute homogeneously in the cytoplasm, a molecular condition that promises benefits for treatment as cytoplasmic and in particular perinuclear enrichment of the radionuclide carriers may better facilitate the radiation-mediated damage of cancerous cells. This study is the first to reveal the subcellular fate of PSMA/PSMA inhibitor complexes at the nanoscale and aims to inspire the development of new approaches in the field of prostate cancer research, diagnostics, and therapeutics. - Significance: This study uses STED fluorescence microscopy to reveal the subcellular fate of PSMA/PSMA inhibitor complexes near the molecular level, providing insights of great clinical interest and suggestive of advantageous targeted therapies. - Graphical Abstract: http://cancerres.aacrjournals.org/content/canres/81/8/2234/F1.large.jpg.
Gesehen am 23.07.2021